Strategi Pengembangan Kelembagaan Kelompok Tani Hortikultura Di Kelurahan Malumbi Kecamatan Kambera Kabupaten Sumba Timur: Staregy For Institutional Development Of Horticulture Farming Groups In Malumbi Village, Kambera District, East Sumba District - Melsyani Sintia Niko; Junaedin Wadu (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
This study aims to identify and understand both internal and external factors that influence the development of horticulture farmer groups in Malumbi Village, Kambera District, East Sumba Regency, and to devise strategies for their development. The research involved 13 respondents selected through purposive sampling. It employed descriptive analysis and the IFAS EFAS SWOT analysis method. The findings from the Internal Factor Evaluation (IFE) Matrix revealed that the primary strength of the farmer group lies in its members' experience and skills in horticulture, scoring 0.397, while the main weakness is a lack of capital for business development, scoring 0.186. The External Factor Evaluation (EFE) Matrix showed that the main opportunity is the rising demand for horticultural products, with a score of 0.397, and the main threat is price instability, scoring 0.271. Based on the Quantitative Strategic Planning Matrix (QSPM) analysis, the top strategy involves collaboration between farmer groups, the government, and financial institutions to secure business capital, with a score of 6.876.